Adaptability and diversity of core microbiome in evaluating the effect of digested versus raw manure in anaerobic digestion of rice straw - Rani J.; Dhoble A.S. (My University, 2025)
The application of anaerobic digestion (AD) for the management of rice straw (RS) provides a way to generate bioenergy to tackle greenhouse gas emissions caused by conventional burning and tilling of straw back into the fields. The existing research often neglects inoculum selectivity and microbial community roles in AD. This study demonstrates the superiority of the microbial community from digested manure (ADS) over raw manure (CD) in producing biogas from rice straw. Notably, the microbial community of digested manure progressively resembled that of raw cow dung after 45 days of anaerobic digestion showing 116 common bacterial genera in comparison to just 9 at the beginning of the experiment. The dominant bacterial genus observed was Clostridiales, with its abundance rising from 9.86% to 38.40% in ADS and declining from 38.16% to 7.53% in CD from day 0 and day 45. This was succeeded by a rise in Prevotella and a reduction in Pseudomonas as the days advanced. Methanobrevibacter was the dominant genus of hydrogenotrophic archaea whose abundance increased from 8.20% to 64.25% in ADS and decreased from 61.41% to 8.98% in CD. Reactors inoculated with ADS outperformed those inoculated with raw CD by producing 7.07 times higher biogas. Additionally, the study highlights the influence of microbial dynamics on volatile fatty acid accumulation, and buffering capacity of the AD system. The significance of this research lies in enhanced microbial activity and digestion rate, reduced start-up time, and adaptation to feedstock resulting in higher biogas production. © 2023 Elsevier Ltd